A Demonstration Model of Interagency Collaboration for Students With Disabilities: A Multilevel Approach. (February 2018) - Flowers, Claudia; Test, David W.; Povenmire-Kirk, Tiana C.; Diegelmann, Karen M.; Bunch-Crump, Kimberly R.; Kemp-Inman, Amy; Goodnight, Crystalyn I.
Communicating Interagency Relationships and Collaborative Linkages for Exceptional Students (CIRCLES) is a transition-planning service delivery model designed to guide schools in implementing interagency collaboration. This study examined the impact of CIRCLES on students' self-determination and participation in individualized education program (IEP) meetings. Forty-four schools located in the Southeast United States were assigned randomly into either the CIRCLES or business-as-usual (BAU) conditions, and 877 high school students with disabilities were included in the analyses. Two-level hierarchical linear models, with students at Level 1 and schools at Level 2, examined the effectiveness of CIRCLES. Results indicated students in the CIRCLES condition had higher levels of self-determination (Hedges's g = .06–.38) and greater IEP participation (Hedges's g = .77). Implications for practice and suggestions for future research are provided.